2017
DOI: 10.18203/2349-3933.ijam20171051
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of coping in patients of alcohol dependence and its correlation with anxiety, depressive symptoms

Abstract: Background: Alcohol use disorder is a common and challenging problem in India. In various studies the prevalence of co-morbid psychopathologies ranges from 15-70% including depression & anxiety disorders. Coping mechanisms of individual play vital role in case of developing alcohol dependence and various psychopathologies. A complex interaction of psychopathologies, coping skills, and alcohol use can influence the outcome of alcohol dependence. This study was undertaken with the aim of studying coping mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous studies reported similar findings that persons with AUD use avoidant approaches and multiple coping strategies (avoidance, substitution, distraction, and religious practices). 10 - 20 More relapsed individuals use escapism and fatalism as coping strategies. Coping strategies differ between abstinent and relapsed alcohol dependents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported similar findings that persons with AUD use avoidant approaches and multiple coping strategies (avoidance, substitution, distraction, and religious practices). 10 - 20 More relapsed individuals use escapism and fatalism as coping strategies. Coping strategies differ between abstinent and relapsed alcohol dependents.…”
Section: Discussionmentioning
confidence: 99%
“…Coping mechanisms play a crucial role in the cause of AUD and various psychopathologies. 10 A variety of coping strategies were used by men with AUD. 11 - 19 Women with AUD use more emotion-focused coping and less problem-focused coping than their male counterparts.…”
mentioning
confidence: 99%
“…There are several impacts of alcohol use among young adults, particularly those who are attending university or college, such as reduced learning capability [ 28 ], deprived coping skills [ 29 ], and condensed social skills [ 30 ]. Several studies [ 15 , 21 , 24 ] have reported that different characteristics such as sex, age, living away from home, parental education, household income, and tobacco use, contribute to the prevalence of alcohol use.…”
Section: Introductionmentioning
confidence: 99%